BUSINESS MODEL DEVELOPMENT AND STRATEGIC INNOVATION FOR STRENGTHENING THE COMPETITIVENESS OF MICRO AND SMALL ENTERPRISES IN INDONESIA - Sunggales Rangga Gustiano; Agus Purnomo (PT. Jurnal Center Indonesia Publisher, 2026)
This study examines the development of business models and strategic innovation as key mechanisms for enhancing the competitiveness of Micro and Small Enterprises (MSEs) in Indonesia. Using a qualitative descriptive approach, the research analyzes how MSEs adapt to changing market dynamics, consumer preferences, and digital transformation pressures. The findings reveal that innovation in value propositions, customer engagement, and digital marketing plays a significant role in improving business performance. The study also highlights that many MSEs have not yet implemented structured business model frameworks, resulting in limited scalability and reduced competitiveness. The analysis is grounded in the Business Model Canvas (BMC) framework, which is used to identify strategic gaps and opportunity areas. The study concludes that strengthening business models through innovation, partnership development, and digital integration can significantly enhance MSE sustainability and long-term competitiveness.